Bacterial Adhesion Strength on Titanium Surfaces Quantified by Atomic Force Microscopy: A Systematic Review - Juliana Dias Corpa Tardelli; Vanderlei Salvador Bagnato; Andréa Cândido dos Reis (MDPI AG, 2023)
Few studies have been able to elucidate the correlation of factors determining the strength of interaction between bacterial cells and substrate at the molecular level. The aim was to answer the following question: What biophysical factors should be considered when analyzing the bacterial adhesion strength on titanium surfaces and its alloys for implants quantified by atomic force microscopy? This review followed PRISMA. The search strategy was applied in four databases. The selection process was carried out in two stages. The risk of bias was analyzed. One thousand four hundred sixty-three articles were found. After removing the duplicates, 1126 were screened by title and abstract, of which 57 were selected for full reading and 5 were included; 3 had a low risk of bias and 2 moderated risks of bias. (1) The current literature shows the preference of bacteria to adhere to surfaces of the same hydrophilicity. However, this fact was contradicted by this systematic review, which demonstrated that hydrophobic bacteria developed hydrogen bonds and adhered to hydrophilic surfaces; (2) the application of surface treatments that induce the reduction of areas favorable for bacterial adhesion interfere more in the formation of biofilm than surface roughness; and (3) bacterial colonization should be evaluated in time-dependent studies as they develop adaptation mechanisms, related to time, which are obscure in this review.